Analisis Daya Saing Ekspor Rumput Laut Indonesia Ke China Dan Korea Selatan - Greyuni Grace Tambunan; Muhammad Aryo Fachrezi; Novia Miftakhul Qisthi; Muhammad Tsaqifa Ifada; Safira Kencana Putri; Rasidin Karo Karo Sitepu; Nur Faizatul Luthfiah (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Seaweed is a leading Indonesian export commodity that has great potential in the fisheries industry. The purpose of this study is to evaluate Indonesia's seaweed export performance and identify factors that affect its competitiveness in the international market, especially in destination countries such as China and Korea. The research method used quantitative and qualitative analysis methods with Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and Export Competitiveness Index (ECI) analysis methods. The data shows that China is the main export destination country for Indonesian seaweed, with a high export contribution of 83% of total exports. South Korea is also an important market, despite fluctuations in export volumes. In addition, this study also revealed the existence of other destination countries such as Chile, Hong Kong, Japan, and the Philippines with varying export contributions each year. Based on the results of the analysis, Indonesian seaweed has a significant comparative advantage in exports to China and Korea, with Korea showing a higher average RCA value over the last five years. EPD analysis indicates that Indonesian seaweed is in a Rising Star position in the Chinese market, signaling a dynamic increase in market share and rapid demand and South Korea is experiencing fluctuations in its competitive position.